Proceedings of the Web Conference 2020 2020
DOI: 10.1145/3366423.3380162
|View full text |Cite
|
Sign up to set email alerts
|

Go See a Specialist? Predicting Cybercrime Sales on Online Anonymous Markets from Vendor and Product Characteristics

Abstract: Many cybercriminal entrepreneurs lack the skills and techniques to provision certain parts of their business model, leading them to outsource these parts to specialized criminal vendors. Online anonymous markets, from Silk Road to AlphaBay, have been used to search for these products and contract with their criminal vendors. While one listing of a product generates high sales numbers, another identical listing fails to sell. In this paper, we investigate which factors determine the performance of cybercrime pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Types of Products and Services. As Wegberg et al [25] found product characteristics influence sales volumes, we investigate the types of products or services being marketed. We qualitatively analyse threads associated with public transactions, which serve as advertisements for a given product or service, to reveal the extent product type drives trade.…”
Section: Cold Start Problemmentioning
confidence: 99%
“…Types of Products and Services. As Wegberg et al [25] found product characteristics influence sales volumes, we investigate the types of products or services being marketed. We qualitatively analyse threads associated with public transactions, which serve as advertisements for a given product or service, to reveal the extent product type drives trade.…”
Section: Cold Start Problemmentioning
confidence: 99%
“…For each of the listings posted by vendors on these markets, the dataset contains information as the title, descriptions, advertised prices, timestamps, and most importantly the feedbacks on each item. Previous research has shown that feedbacks have proven to be a good proxy for sales, and provide a structural lower bound of sales [2], [4], [7], [19]. Combining both datasets enables us to link numerous pseudonyms across multiple dark markets and aggregate careers through the proxy of PGP-keys.…”
Section: Datamentioning
confidence: 99%
“…Prior research has been done on analyzing a broad spectrum of criminal career trajectories -ranging from burglars, to homicide offenders and even mafia organizations [23]- [27]. From earlier work we know that vendors have individual characteristics, which influence their success on dark net markets and ultimately determine the length and strength of their career [4].…”
Section: B Group-based Trajectory Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have focused on the profits made by the criminals facilitating digital products from business-tobusiness [10], [11] but neglected the trades in these markets targeting directly consumers. On the other hand, a handful number of qualitative studies focused on understanding criminals and victims of particular types of fraud without quantifying its financial impact (e.g., airline ticketing fraud [12]).…”
Section: Introductionmentioning
confidence: 99%